Protein Kinase Inhibitor Peptide as a Tool to Specifically Inhibit Protein Kinase A - Liu, Chong; Ke, Ping; Zhang, Jingjing; Zhang, Xiaoying; Chen, Xiongwen (Frontiers in Physiology, 2020)
The protein kinase enzyme family has been considered nowadays to play a pivotal role in almost every aspect of cellular function, including cellular metabolism, division, proliferation, transcription, movement and survival. Protein kinase A (PKA), whose activation is triggered by cAMP, is widely distributed in various systems and tissues throughout the body and highly related to pathogenesis and progression of various kinds of diseases. The inhibition of PKA activation is essential the study of PKA features. Protein kinase inhibitor peptide (PKI) is a heat-stable interfering substance. It has been demonstrated that PKI can block PKA-mediated phosphorylase kinase activation. Since that, much knowledge on PKI has been obtained by researchers, the method taking advantage of PKI have been regarded as the most effective and specific one in the inhibition of PKA and widely used in the related fundamental studies. Here in this review, we will first introduce the knowledge on the activation of PKA and mechanisms on the inhibitory effects of PKI on PKA. Then, we will compare PKI-mediated PKA inhibition versus several popular methods on PKA inhibition.